Athletic goal achievement: A critical antecedent of event satisfaction, re-participation intention, and future exercise intention in participant sport events. Issue 2 (April 2020) - Hyun, Moonsup; Jordan, Jeremy S.
Highlights: Athletic performance is a predictor of participant sport events satisfaction. Service quality and perceived value are important predictors of event satisfaction. Achieving athletic performance goals increases re-participation intention. Achieving athletic performance goals increases future exercise intention. Performance goal importance does not moderate the effect of athletic performance. Abstract: The purpose of this study is to develop a comprehensive understanding of consumer experiences in participant sport events. The authors explored two traditionally prominent components (i.e., service quality and perceived economic value) and one emerging factor (i.e., athletic goal achievement) of consumer experiences at participant sport events. The authors examined the effects of these three factors on re-participation intention and the effect of athletic goal achievement on future exercise intention. Results of moderated serial mediation analyses based on data from a sample of marathon runners ( N = 3186), all three factors exerted significant effects on re-participation intention. In particular, athletic goal achievement was positively associated with re-participation intention and future exercise intention through the serial mediation of performance satisfaction and overall event satisfaction. However, the moderating effects of athletic goal importance on the serial indirect relationship between athletic goal achievement and two outcome variables (i.e., re-participation intention and future exercise intention) were not significant. The findings of this study offer participant sport service providers with insights to manage participants' athletic performance, service quality, and perceived economic value for better consumer experiences. Such efforts should result in higher participant satisfaction, better retention rates, and a higher post-event physical activity level.